1996
DOI: 10.1523/jneurosci.16-24-08057.1996
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Treatment with Δ9-Tetrahydrocannabinol on Cannabinoid-Stimulated [35S]GTPγS Autoradiography in Rat Brain

Abstract: Chronic Delta9-tetrahydrocannabinol (Delta9-THC) administration produces tolerance to cannabinoid effects, but alterations in signal transduction that mediate these changes are not yet known. The present study uses in vitro autoradiography of agonist-stimulated [35S]GTPgammaS binding to localize cannabinoid receptor-activated G-proteins after chronic Delta9-THC treatment. Cannabinoid (WIN 55212-2)-stimulated [35S]GTPgammaS binding was performed in brain sections from rats treated chronically with 10 mg/kg Delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
178
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(195 citation statements)
references
References 26 publications
16
178
1
Order By: Relevance
“…It has already been established that chronic cannabis users assessed during periods of abstinence demonstrate hypoactive cerebellar activity, which could be interpreted as neuroadaptive endocannabinoid downregulation (Volkow et al, 1996;Block et al, 2000;Chang et al, 2006). Indeed, animal studies have shown that behavioral tolerance to the motor effects of THC is likely mediated by CB1 downregulation throughout the cerebellum (Sim et al, 1996;Romero et al, 1998). More recently, it has been found that chronic cannabis use in humans does in fact lead to significant CB1 downregulation as determined via postmortem [ 3 H]SR141716A binding (Villares, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been established that chronic cannabis users assessed during periods of abstinence demonstrate hypoactive cerebellar activity, which could be interpreted as neuroadaptive endocannabinoid downregulation (Volkow et al, 1996;Block et al, 2000;Chang et al, 2006). Indeed, animal studies have shown that behavioral tolerance to the motor effects of THC is likely mediated by CB1 downregulation throughout the cerebellum (Sim et al, 1996;Romero et al, 1998). More recently, it has been found that chronic cannabis use in humans does in fact lead to significant CB1 downregulation as determined via postmortem [ 3 H]SR141716A binding (Villares, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Purkinje cells activated by glutamatergic granule cells normally serve to inhibit cerebellar deep nuclei (ie interpositus nucleus) thus modulating the timing of conditioned blink responses (CRs) (Steinmetz, 2000). Chronic cannabis use, which is known to produce behavioral tolerance and may induce long-term endocannabinoid compensatory changes (eg CB1 downregulation; Sim et al, 1996;Romero et al, 1998), could result in increased granule cell glutamate release, and hence overactive inhibitory Purkinje inputs to the interpositus. This position is in agreement with a recent study of CB1 knockout animals, in which mice lacking the CB1 receptor exhibit severely disrupted EBC (Kishimoto and Kano, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a hypoactivation in this area might indicate some deficits in long-term memory storage, at least in the first stages of its initial consolidation. Sim et al (1996) reported decreases in WIN-stimulated GTPg 35 S binding in the entorhinal cortex after a chronic THC treatment. This desensitization of CB1 receptors might account for the hypoactivation observed in this brain region.…”
Section: Adolescent Cannabis and Adult Cocaine Addictionmentioning
confidence: 98%
“…Animal studies lend some credibility to this theory; however, results are not consistently reproducible in human studies. Additionally, many inferential hypotheses were identified that attribute different aspects of CHS to a myriad of dysregulatory issues at CB-1 receptors throughout the body (brain, gastrointestinal tract, and vasculature) [97,98,102,105,133,[135][136][137]. The experimental evidence behind these inferences illustrates the complexity of the pathophysiology of CHS and raises many additional questions.…”
Section: Pathophysiology Of Chsmentioning
confidence: 99%